Influence of age of rooted cutting, nitrogen and stage of harvest on growth, yield and quality of patchouli [Pogostemon cablin (Blanco) Benth.] - K V N S Srinivas, M Singh, (Journal of Spices and Aromatic Crops, 2014)
Field experiments were conducted to study the influence of age of rooted cuttings at the time of planting (30, 40, 50, 60, 70, 80 and 90 days), N levels (0, 50 and 100 kg ha-1) and stage of harvest (once in 4, 5 and 6 months) on yield and oil quality of patchouli [Pogostemon cablin (Blanco) Benth.] under semi-arid tropical climate. The results indicated that planting 30 day old rooted cuttings produced higher plant height, plant canopy and oil yield compared with other treatments. Similarly, application of 100 kg N ha-1 and stage of harvest after six months of planting produced maximum herbage yield, oil yield and oil content compared to other treatments. The highest net return (Rs. 59,550 ha-1) and B:C ratio (1.168) were recorded with the application of 100 kg N ha-1 and stage of harvest once in six months. Oil quality was not influenced by age of the rooted cuttings and N level.